Expanding Access: Cost‐effectiveness of Cochlear Implantation and Deaf Education in Asia. (18th June 2019) - Emmett, Susan D.; Sudoko, Chad K.; Tucci, Debara L.; Gong, Wenfeng; Saunders, James E.; Akhtar, Nasima; Bhutta, Mahmood F.; Touch, Sokdavy; Pradhananga, Rabindra Bhakta; Mukhtar, Nadeem; Martinez, Norberto; et al.
Abstract : Objective: To determine the cost‐effectiveness of cochlear implantation (CI) with mainstream education and deaf education with sign language for treatment of children with profound sensorineural hearing loss in low‐ and lower‐middle income countries in Asia. Study Design: Cost‐effectiveness analysis. Setting: Bangladesh, Cambodia, India, Indonesia, Nepal, Pakistan, Philippines, and Sri Lanka participated in the study. Subjects and Methods: Costs were obtained from experts in each country with known costs and published data, with estimation when necessary. A disability‐adjusted life‐years model was applied with 3% discounting and 10‐year length of analysis. A sensitivity analysis was performed to evaluate the effect of device cost, professional salaries, annual number of implants, and probability of device failure. Cost‐effectiveness was determined with the World Health Organization standard of cost‐effectiveness ratio per gross domestic product (CER/GDP) per capita <3. Results: Deaf education was cost‐effective in all countries except Nepal (CER/GDP, 3.59). CI was cost‐effective in all countries except Nepal (CER/GDP, 6.38) and Pakistan (CER/GDP, 3.14)—the latter of which reached borderline cost‐effectiveness in the sensitivity analysis (minimum, maximum: 2.94, 3.39). Conclusion: Deaf education and CI are largely cost‐effective in participating Asian countries. Variation in CI maintenance and education‐related costs may contribute to the range of cost‐effectiveness ratios observed in this study.